Model Manajemen Kepala Sekolah Dalam Mengembangkan Kompetensi Profesional Guru Di SMP Nur Adia Tanjung Selamat Deli Serdang - Naddya, Anisa; Akrim, Akrim (UMSU, 2024)
This study aims to determine the principal's management model in developing teachers' professional competence at Nur Adia Tanjung Selamat Junior High School in Deli Serdang, with a qualitative research type. The method of collecting data is observation, interviews and documentation and uses data analysis techniques of data collection, data reduction and conclusions. The results showed that the principal's management planning model in developing teachers' professional competence was involved in a formal strategy which was planned and implemented at SMP Nur Adia Tanjung Selamat including leadership as an educator leadership manager and principal as a leader. The implementation of Principal Management must be right on target with the division of labour that has been determined. Related to teacher competence at SMP Nur Adia Tanjung Selamat. Evaluating the principal encourages teachers to be creative and innovative by taking several approaches to teachers and staff teachers who are at SMP Nur Adia Tanjung Selamat. The evaluation carried out is to make approaches by familiarising themselves with the teacher, for example visiting the teacher's room.